Peran dan Potensi Wakaf Uang dalam Pembentukan Bank Wakaf untuk Pengentasan Kemiskinan Berbasis Pesantren di Pondok Pesantren Al Amanah Al Gontory - Achmad Dzikri Rajuli; Iltizam Umma Aqelia Hayatunnufus; Azzam, Ahmad (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2024)
The research conducted focuses on discussing the role and potential of cash waqf collected by sharia cooperatives, then after the collected cash waqf funds are handed over to the waqf bank for management in Islamic boarding school-based poverty alleviation efforts. There are two methods used in this research, First is a library study (Library Research) towards books and reading materials related to the discussion. Second is a field study using natural direct observation to obtain more valid data, including: observation, interviews, and interaction with participants who represent the research object. The results of research on the role and potential of cash waqf in the formation of waqf banks for Islamic boarding school-based poverty alleviation show that sharia cooperatives that are present in Islamic boarding school-based educational institutions can be the spearhead in collecting cash waqf because to carry out cash waqf you don't need to wait to be rich or established, anyone it is possible to carry out cash waqf with a small nominal amount such as five thousand rupiah, so that with the collected waqf capital the money that has been collected can be used to establish a waqf bank whose management must be in accordance with the purpose of its formation, such as making investments by providing convenience in terms of financing to the community. around Islamic boarding schools with small profit sharing so that it does not burden the customers, the waqf bank apart from providing financing has another very important role in supervising customers, namely by empowering, spiritual and physical development with religious knowledge and sharia-based family financial planning and providing business assistance so that the objectives of the financing can be achieved in accordance with the plans that have been prepared Keywords: waqf banks, cash waqf, empowerment, financing, poverty, sharia cooperatives.